Sloshing Loads on the Head of an Annular Cylindrical Reactor Vessel. (1st February 2023) - Mir, Faizan Ul Haq; Nguyen, Nam; Song, Brian; Kosbab, Benjamin; Whittaker, Andrew S.
Abstract: The head of a cylindrical reactor vessel must be designed for earthquake-induced sloshing force if there is insufficient freeboard. Herein, a design-oriented calculation method is developed for base-and head-supported annular tanks, where the annulus separates the reactor vessel and its core barrel. Charts are provided to enable preliminary design calculations. Examples are presented to describe the calculations.